2023
DOI: 10.1029/2023gl104726
|View full text |Cite
|
Sign up to set email alerts
|

Potential Non‐Linearities in the High Latitude Circulation and Ozone Response to Stratospheric Aerosol Injection

Ewa M. Bednarz,
Daniele Visioni,
Amy H. Butler
et al.

Abstract: The impacts of Stratospheric Aerosol Injection (SAI) on the atmosphere and surface climate depend on when and where the sulfate aerosol precursors are injected, as well as on how much surface cooling is to be achieved. We use a set of CESM2(WACCM6) SAI simulations achieving three different levels of global mean surface cooling and demonstrate that unlike some direct surface climate impacts driven by the reflection of solar radiation by sulfate aerosols, the SAI‐induced changes in the high latitude circulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Changes to stratospheric temperatures as a result of SAI can drive changes in stratospheric ozone, due to changes in both stratospheric dynamics and chemistry. Studies have shown that enhancements of the stratospheric sulfate aerosol layer from SAI would increase the aerosol surface area density, influencing halogen activation in the lower stratosphere and the removal of active nitrogen species in the middle stratosphere, thereby modulating chemical ozone loss (Bednarz et al, 2023a(Bednarz et al, , 2023bTilmes et al, 2018aTilmes et al, , 2022. In addition, the SAI-induced lower stratospheric heating will also influence ozone via changes in the large scale transport as well as through increased stratospheric water vapor levels and thus chemical ozone loss.…”
Section: Stratospheric Ozonementioning
confidence: 99%
See 1 more Smart Citation
“…Changes to stratospheric temperatures as a result of SAI can drive changes in stratospheric ozone, due to changes in both stratospheric dynamics and chemistry. Studies have shown that enhancements of the stratospheric sulfate aerosol layer from SAI would increase the aerosol surface area density, influencing halogen activation in the lower stratosphere and the removal of active nitrogen species in the middle stratosphere, thereby modulating chemical ozone loss (Bednarz et al, 2023a(Bednarz et al, , 2023bTilmes et al, 2018aTilmes et al, , 2022. In addition, the SAI-induced lower stratospheric heating will also influence ozone via changes in the large scale transport as well as through increased stratospheric water vapor levels and thus chemical ozone loss.…”
Section: Stratospheric Ozonementioning
confidence: 99%
“…Whilst there are some differences between a single pulse injection of SO 2 from a volcanic eruption and the continual injection needed to consistently cool the planet (MacMartin et al., 2016; Robock et al., 2013), volcanic eruptions act as natural analogs for assessing the capability of global climate models to model SAI (e.g., Trenberth & Dai, 2007). Model uncertainties (Bednarz et al., 2023c; Henry et al., 2023; Niemeier & Timmreck, 2015; Visioni et al., 2021, 2023a) and different SAI scenario choices, including the choice of baseline emissions scenario (Fasullo & Richter, 2023), injection location or strategy (Bednarz et al., 2023a; Franke et al., 2021; Heckendorn et al., 2009; Kravitz et al., 2019; Zhang et al., 2024), temperature target (Bednarz et al., 2023b; Hueholt et al., 2023; MacMartin et al., 2022; Visioni et al., 2023b) and timing of SAI deployment (Brody et al., 2024) can result in different large‐scale climate responses and the associated regional impacts.…”
Section: Introductionmentioning
confidence: 99%